OBESITY AND MOTOR DEVELOPMENT - A CROSS-SECTIONAL STUDY WITH BRAZILIANS SCHOOL CHILDREN (Fiep Bulletin - online, 2014)
The obesity in childhood is associated with several problems related to the health in the adult life. Evidences exist that psychomotor development of obese children is wronged in detriment of the body scheme disorders. The objective of this study is evaluate the motor development of obese children. A total of 194 obese primary-school children aged 6-10 years, of both sexes, were selected. The data had been collected in three schools of São Jose (Santa Catarina). The 90th percentile for BMI/Age was used  to classify the children with obesity, and the Scale of Motor Development (Rosa Neto, 2001) was used to evaluate the motor development. In the statistical treatment it was used descriptive statistics and the software Epi info. Results:  the obese school children of this study showed inferior motor development  for its chronological age. The areas that had presented greater deficit had been temporal organization, space organization and balance. We believe that obese children do not have an conformed motor stimulation for its development, and that this can be related to the lifestyle of the same ones.